2020
DOI: 10.3389/fnins.2019.01424
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Gray and White Matter Structural Substrates of Sex Differences in the Narrative Abilities of Healthy Adults

Abstract: Inter-Sex Brain and Language Differences verb frequency was significantly higher for women, but no differences were identified for MLU. Regarding cortical measures, males demonstrated increased volume, surface area and cortical thickness in several bilateral regions, while no voxel-wise or tractographybased between-group differences in white matter metrics were observed. Regarding the relationship between sex and speech variables, hierarchical regression analyses showed that the superior/middle frontal cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 92 publications
(120 reference statements)
4
15
0
Order By: Relevance
“…In support of our findings, early analyses stratified by sex suggested that men have a symmetrical increase in white matter volume and concentration in the bilateral anterior temporal lobe (Good et al, 2001). Our findings receive further support in that healthy male volunteers showed increased grey matter volume and cortical thickness in several bilateral regions relative to females, although no relationship with speech tests was reported (Angelopoulou et al, 2019;Ritchie et al, 2018). Notably, previous studies are inconclusive with respect to sex incongruencies in functional and structural substrates of language-related processes (Ullman et al, 2007;Xu et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…In support of our findings, early analyses stratified by sex suggested that men have a symmetrical increase in white matter volume and concentration in the bilateral anterior temporal lobe (Good et al, 2001). Our findings receive further support in that healthy male volunteers showed increased grey matter volume and cortical thickness in several bilateral regions relative to females, although no relationship with speech tests was reported (Angelopoulou et al, 2019;Ritchie et al, 2018). Notably, previous studies are inconclusive with respect to sex incongruencies in functional and structural substrates of language-related processes (Ullman et al, 2007;Xu et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…In the case of long silent intervals, the examiners provided the patients with minimal encouragement to continue the narration. In case the patients did not respond, narration assessment was stopped (for a detailed description, see Angelopoulou et al, 2020 ; Kasselimis et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of long silent intervals, the examiners provided the patients with minimal encouragement to continue the narration. In case the patients did not respond, narration assessment was stopped (for a detailed description, see Angelopoulou et al, 2020;Kasselimis et al, 2020). Additionally, the Greek version of the Boston Naming Test (BNT; Simos et al, 2010) and a receptive vocabulary test, the Greek version of the Peabody Picture Vocabulary Test-Revised (PPVT-R; Simos et al, 2010) were used, including the Controlled Oral Word Fluency (COWF) test (Kosmidis et al, 2004), a verbal fluency task standardized in Greek.…”
Section: Neuropsychological Evaluationmentioning
confidence: 99%
“…The truth is that there are some differences in brain structure and function between the sexes regardless of data from previous studies being divergent. It has been surmised that the male brain is generally larger in volume and that females have a proportionally larger amount of grey matter in comparison with white matter in different compartments of the brain [28]. Differences in brain function may also indicate a contribution to a decline in cognition, as females acquire a higher activity in the sensory association cortex of the parietal lobe, while males in the motor and visual cortices [29].…”
Section: Sex Differences In Neurologic Diseasesmentioning
confidence: 99%